Factor Analysis Of Employee Engagement On Employees At PT XYZ - Najla Khalisa, Kamila; Dudija, Nidya (Publisher Cv. Inara, 2025)
This research aims to identify the factors that represent employee engagement at PT. XYZ, model fit, and the emergence of new engagement factors. This research uses quantitative method with a cross-sectional survey of 312 respondents, was conducted using a convenience sampling and 5 scale of Likert for the questionnaire. Data analysis includes descriptive statistics, factor analysis consisting of EFA and CFA. In the process, the analysis was conducted using SPSS and AMOS. The results of this study state that the factors that represent employee engagement at PT. XYZ is Personal Growth & Work Life Balance. The quality of model adjustment values are fit. The identification of new factors that emerged in this study, namely the Agile & Smart Workplace. This study offers a more comprehensive discussion than previous studies by analyzing a large number of factors and indicators through EFA and CFA analysis in stages. To better engage employees, managers is advised to maintain or even improve the factor that represent the engagement of PT. XYZ, develop strategies to formulate more structured employee engagement policies based on data, and create a smart workplace with the practice of utilizing technology and digitalization.